PROGRAM AMALIYAH TADRISDANKEMAMPUANMENGAJAR BERBAHASA ARAB DI TARBIYATUL MUALLIMIEN AL-ISLAMIYAH PONDOK PESANTREN NURUL HUDA DESA PAKANDANGAN BARAT KECAMATAN BLUTO KABUPATEN SUMENEP TAHUN 2015 - Mufiqur Rahman (Sekolah Tinggi Ilmu Tarbiyah Al - Ibrohimy Bangkalan, 2016)
Aim of this researh devided into two kinds. To know The Correlation Between Teaching Practice Program With Teaching Ability Of Practitioner StudentTarbiyatul Muallimien Al-Islamiyah Boarding School Nurulhuda West Village District Sub District Bluto Regency Sumenep 2015. And to know how The Correlation Between Teaching Practice Program With Teaching Ability Of Practitioner StudentTarbiyatul Muallimien Al-IslamiyahBoarding School Nurulhuda West Village District Sub District Bluto Regency Sumenep 2015. The remark obtained by this researh indicates that teaching practise program is correlated possitivelly and efectivelly With Teaching Ability Of Practitioner StudentTarbiyatul Muallimien Al-IslamiyahBoarding School Nurulhuda West Village District Sub District Bluto Regency Sumenep 2015. And The Correlation Between Teaching Practice Program With Teaching Ability Of Practitioner StudentTarbiyatul Muallimien Al-IslamiyahBoarding School Nurulhuda West Village District Sub District Bluto Regency Sumenep 2015 is mediun category.